Improved synthesis and transient absorption spectroscopy of CuBiW2O8 with demonstration of visible-light-driven photocatalysis and mechanistic insights. Issue 46 (26th October 2022) - Yilmaz Akkaya, Ceren; Dombrowski, James P.; Colin-Ulloa, Erika; Titova, Lyubov V.; Lawton, Timothy J.; Alexander, Todd E.; Brack, Eric; Drew, Christopher; Rao, Pratap M.
Abstract : CuBiW2 O8 (CBTO), with a band gap of 1.9–2.0 eV, responds to a wide region of the electromagnetic spectrum has been demonstrated as a photocatalyst with high activity for Cr(vi ) reduction. Abstract : CuBiW2 O8 (CBTO), with a band gap of 1.9–2.0 eV, responds to a wide region of the electromagnetic spectrum, which makes it a good candidate for solar-driven photocatalytic energy conversion and water treatment. We have previously demonstrated a Cu-rich solid state approach that enables the synthesis of CBTO accompanied by thermodynamically stable Bi2 WO6 impurity. Here, we describe an improved synthesis protocol with decreased impurity and synthesis time, and the first demonstration of CBTO as a functional material using photocatalytic Cr(vi ) photoreduction as a probe reaction. Transient absorption spectroscopy (TAS) was performed to investigate the ultrafast dynamics of the charge carriers after photoexcitation. The presence of two populations of photoexcited carriers was found, including short-lived free carriers with ∼10 ps lifetime and long-lived shallowly-trapped carriers with ∼1 ns lifetime. Together with carrier mobilities measured in our previous study, the new TAS results indicate that the long-lived charges have diffusion lengths similar to the CBTO particle size and were likely responsible for the majority of the photocatalytic activity. High activity of CBTO for Cr(vi ) photoreduction (∼100% reduction of 5 mg L −1 of Cr(vi ) in 15 minutes) was demonstrated, which clearly establishes the promise of this novel oxide for visible light-driven photocatalytic applications. Radical quenching experiments indicate that both ˙OH radicals and O2 ˙ − radicals are produced by CBTO and are involved in the photoreduction of Cr(vi ). Repeated photocatalysis tests and analysis of the surface after the reaction show that CBTO is a stable and potentially reusable catalyst. Insights gained from correlating the synthesis conditions, carrier dynamics, and reactive species suggests that CBTO prepared with the improved protocol would be a favorable choice for photocatalytic reactions such as water decontamination from organic pollutants, water splitting, and solar fuel generation using visible light.